Recent events in the euro area and the forthcoming membership of Poland - Belka, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The future of the euro area is like the Leaning Tower of Pisa. Invariably intriguing, it requires strengthening that would prevent it from leaning out even further. Likewise, the euro area needs strengthening. Once the process is completed, we will be able to resume our deliberations as to the best timing for Poland's accession to the euro area. One might ask whether not being part of the euro area is generating costs for the Polish economy. Well, this is not the right question to ask. Recent traumatic experiences of several euro area countries pose a different question: how should the euro area change and how should we prepare to join so that our economy benefits? My lecture today is divided into two parts. First, I shall run briefly through the causes of the severe disturbances which have recently occurred in the euro area. The second part of the lecture will deal with factors to be considered when considering Poland's accession to the euro area
Argumenta Oeconomica, 2012, Nr 1 (28), s. 5-12
Keywords: kryzys finansowy; polityka walutowa; strefa euro; financial crisis; monetary policy; eurozone